2017
DOI: 10.1101/136960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying core biological processes distinguishing human eye tissues with precise systems-level gene expression analyses and weighted correlation networks

Abstract: The human eye has several specialized tissues which direct, capture, and pre-process information to provide vision. RNA-seq gene expression analyses have been used extensively, for example, to profile specific eye tissues and in large consortium studies, like the GTEx project, to study tissue-specific gene expression patterning. However, there has not been an integrated study of multiple eye tissues expression patterning with other human body tissues. We have collated current publicly available healthy human R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In contrast to skin, melanin pigment in RPE was shown to be synthesized prenatally and stored in melanosomes throughout life, while tyrosinase activity in adult RPE remained controversial (57,58). Our study provides additional insight: our query of EyeIntegration data (32) found TYR expressed in adult human RPE, which may influence melanin production and its protective function in retina. Therefore, variants in or near TYR may represent risk factors beyond fetal melanin production.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In contrast to skin, melanin pigment in RPE was shown to be synthesized prenatally and stored in melanosomes throughout life, while tyrosinase activity in adult RPE remained controversial (57,58). Our study provides additional insight: our query of EyeIntegration data (32) found TYR expressed in adult human RPE, which may influence melanin production and its protective function in retina. Therefore, variants in or near TYR may represent risk factors beyond fetal melanin production.…”
Section: Discussionmentioning
confidence: 66%
“…These findings support the idea that the credible set captures the essential signal. (4) We queried the 17 genes overlapping the two loci for expression in eye tissue and cells in EyeIntegration summary data (43). We found five and three genes, respectively, expressed in adult retina and adult RPE cells ( CD46, PLXNA2, CR1, CD34, CD55 ; TYR, GRM5, NOX4 ; Figure S7-S8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TRPM3 has been immuno-localized to subdomains of the apical plasma membrane of human fetal RPE cells with particular enrichment at apical tight junctions and the base of primary cilia [136]. RNA sequencing confirms that TRPM3 is more abundant in human RPE tissue and cell lines and a lens stem cell line than in retinal or corneal derived cells [137,138].…”
Section: Human Trpm3_mir204mentioning
confidence: 95%
“…Most of the current (and limited) information we have on eye immunity comes from mammalian models; we know very little about immune processes in the eye of other taxa [68,69,76,77]. More studies targeting multiple eye tissues [78] are therefore clearly needed to evaluate the "immunopriviliged" status of sh eyes in response to eye parasites.…”
Section: Differential Expression Of Immune Genesmentioning
confidence: 99%